The effects of ilioinguinal nerve block on acute and chronic neuropathic pain in patients following inguinal hernia repair with spinal anesthesia: A prospective cohort study - Onur, Tuğba; Karaca, Ümran; Ökmen, Korgün; Terkanlıoğlu, Serkan; Onur, Anıl (Journal of Surgery and Medicine, 2022)
Background/Aim: Post-surgical pain is a major factor affecting the quality of life of patients. This study aims to investigate the effectiveness of ilioinguinal block on acute and chronic neuropathic pain after inguinal hernia surgery with spinal anesthesia. Methods: This prospective cohort study included sixty ASA I-III patients aged 18-65 years, who underwent a unilateral inguinal hernia operation. The patients were divided into two groups: Those who received spinal block only (Group 1, n=30), and those who received spinal and ultrasound-guided ilioinguinal nerve block (Group 2, n=30). The perioperative and postoperative complications, Visual Analogue Scale (VAS) scores on rest and Leeds Assessment of Neuropathic Symptoms and Signs (LANSS) scores at the postoperative 2nd, 6th, 12th, and 24th hours, and in the 3rd and 6th months were noted. Results: No significant difference was observed in the time of first analgesic administration among the groups, but tramadol use significantly reduced in Group 2 (P=0.019). Time until mobilization and discharge was significantly shorter among the Group 2 patients (P<0.001, P=0.021, respectively). Visual Analogue Scale scores at rest at the 12th and 24th hours, and in the 3rd and 6th months were significantly less in Group 2 (P=0.032, P=0.005, P=0.022, P=0.008, respectively). Leeds Assessment of Neuropathic Symptoms and Signs scores of the patients at the 24th hour, 3rd, and 6th months were significantly lower in Group 2 (P<0.001, P<0.001, P=0.012, respectively). Conclusion: We think that ilioinguinal nerve block with spinal anesthesia is a successful and reliable technique for acute postoperative and chronic neuropathic pain management in unilateral inguinal hernia repair.